Prostacyclin analogues: the next drug-eluting stent?. (25th October 2007) - McCormick, C.; Wadsworth, R.M.; Jones, R.L.; Kennedy, S.
Abstract : Recent concern over existing drug-eluting stents, for the treatment of myocardial ischaemia, has led to the development of approaches that seek to inhibit restenosis while promoting the recovery of a functional endothelium. Prostacyclin analogues may be worthy candidates for use within a drug-eluting stent by virtue of their wide profile of vasoprotective effects. This article reviews recent developments in this area, and in so doing, reveals the future challenges for the further development of this technology.